Activation of the TCA Cycle to Provide Immune Protection in Zebrafish Immunized by High Magnesium-Prepared Vibrio alginolyticus Vaccine - Yang, Jun; Yang, Xiao-li; Su, Yu-bin; Peng, Xuan-xian; Li, Hui (Frontiers in Immunology, 2021)
Vaccines are safe and efficient in controlling bacterial diseases in aquaculture industry and are in line with green farming. The present study develop a previously unreported approach to prepare a live-attenuated V. alginolyticus vaccine by culturing bacteria in high concentration of magnesium to attenuate bacterial virulence. Furthermore, metabolome of zebrafish immunized with the live-attenuated vaccine was compared with those of survival and dying zebrafish infected by V. alginolyticus. The enhanced TCA cycle and increased fumarate were identified as the most key metabolic pathways and the crucial biomarker of vaccine-mediated and survival fish, respectively. Exogenous fumarate promoted expression of il1β, il 8, il21, nf-κb and lysozyme in a dose-dependent manner. Among the five innate immune genes, the elevated il1β, il8, and lysozyme are overlapped in the vaccine-immunized zebrafish and the survival from the infection. These findings highlight a way in development of vaccines and exploration of the underlying mechanisms.